A survey of media resources in colleges and universities in Manila with implication for resource sharing - Angeles, Cherry N.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1996)
This study is the first survey conducted to determine the status of media resources of colleges and universitiesin Manila with implication for resource sharing. The study also seeks to find out the strengths and weaknesses of their present audiovisual collection in meeting the needs of the users; their plans for future development; the resource sharing activities they are engaged in and the possible benefit they will acquire from these resource sharing activities.
Seven colleges and universities in Manila were surveyed namely; Far Eastern University (FEU), University of the East (UE), Centro Escolar University (CEU), San Sebastian College (SSC), San Beda College (SBC), La Consolacion College (LCC) and College of the Holy Spirit (CHS). Of the seven colleges and universities surveyed, only six responded. Centro Escolar University failed to return the survey questionnaire. The survey questionnaires were answered either by the head librarian or the audiovisual librarian of each school. Additional interviews and observations of their audiovisual centers were also conducted to further verify questions.
The survey findings showed that all the six colleges and universities have an existing audiovisual center but their collections of media materials and equipment are not sufficient to meet the needs of their users. Resource sharing is also possible among the respondent libraries since they are geographically near each other but they still need to develop their collections and personnel in order for them to network. Networking will be more advantageous to those libraries with lesser collection and less beneficial to those who already have sufficient collection.
Typescript.
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Academic libraries--Philippines--Manila.; Libraries--Special collections--Philippines--Manila.